Development of a multi-dimensional measure for assessing entrepreneurial ecosystems. Issue 1 (1st January 2019) - Liguori, Eric; Bendickson, Josh; Solomon, Shelby; McDowell, William C.
ABSTRACT: Researchers and theorist have put great effort into defining and examining entrepreneurial ecosystems and how business clusters develop in certain regions. Favourable entrepreneurship ecosystems are thought to drive business and innovation. However, a commonly accepted measure of entrepreneurial ecosystem favourableness has yet to be developed. The purpose of the present research is to contribute to ecosystems research by taking a two-study approach to developing and validating a perceptual measure of entrepreneurial ecosystems. The perceptual measure is based upon prior conceptual frameworks that outline ecosystems. In developing this measure, we are able to further unpack and illuminate the factor structure of ecosystems, the results of which have direct scholarly and practitioner uses.